Outcomes of thoracic endovascular aortic repair with chimney technique for aortic arch diseases - Li, Jiehua; Xue, Yunfei; Li, Shangqian; Sun, Likun; Wang, Lunchang; Wang, Tun; Fang, Kun; Luo, Mingyao; Li, Xin; He, Hao; Li, Ming; Li, Quanming; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: To summarize the long-term experience of using chimney technique in thoracic endovascular aortic repair (TEVAR) for aortic arch diseases. Methods: From November 2007 to June 2021, a total of 345 consecutive patients (mean age 56.0±11.3 years, range 28–83, 302 men) with aortic arch pathologies underwent TEVAR combined with chimney technique (cTEVAR). Their medical data and follow-up results were retrospectively reviewed and analyzed. Results: Among the 345 patients, 278 (80.6%) received single chimney, 53 (15.4%) received double chimneys, 7(2%) received triple chimneys, and 7(2%) underwent cTEVAR accompanied with other techniques (2 with extra-anatomical bypass, 2 with in-situ fenestration, and 3 with physician modified fenestration). A total of 412 chimney stents were used, including 27 in innominate artery, 113 in left common carotid artery, 270 in left subclavian artery and 2 in aberrant right subclavian artery. Early type Ia endoleaks were found in 38 (11%) patients, including 12 with double or triple chimney technique. Early type II endoleak were found in 9 (2.6%) patients. Early re-intervention occurred in 2 patients with double chimney technique, one for chimney stent migration and the other for compression of chimney stent. The 30-day mortality was 1.2% (4 in 345). During a mean follow-up of 42±22 months (range 1-108 months), major stroke occurred in 9 (2.6%) patients, chimney occlusion or stenosis occurred in 6 (1.7%), and retrograde type A aortic dissection occurred in 4 (1.2%). Fourteen (4.1%) patients received secondary intervention. The all-cause mortality was 6.7% (23 in 345). And the total adverse event rate after cTEVAR was 13.9% (48 in 345). Conclusions: TEVAR with chimney technique provides a minimally invasive alternative with good chimney graft patency and low postoperative mortality during follow-up. However, the double and triple chimney techniques should be used cautiously as they seem to have higher risk for type Ia endoleak and adverse events after operation.